2019
DOI: 10.26444/aaem/105798
|View full text |Cite
|
Sign up to set email alerts
|

Work safety interventions and threat complexity – A formative investigation into why farmers do not act safely

Abstract: Introduction. Fear appeals are a common tactic used in work safety interventions to motivate farmers to adopt safer behaviours. They begin by introducing a threat, followed by information on how to remove the threat. However, fear appeals tend to be ineffective when developed without a firm grasp of the cognitive processes underlying behavioural change. Although previous research on farm safety interventions have investigated fear appeals, they have focused on very narrow threats and behaviours, such as tracto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…This paper describes the systematic development of an intervention to improve tractor-related safety on farms and aims to fill the lack of theoretically based and adequately described behaviour change-based interventions in the relevant literature [ 4 , 12 , 60 ]. Tractor safety is a complex process involving the interactions between tractor design, farmers’ behaviour and environmental factors [ 6 , 19 , 31 ]. The previous studies indicate that the focus of the safety interventions was on increasing the adoption of engineering solutions, introducing safety regulations and raising risk awareness [ 4 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper describes the systematic development of an intervention to improve tractor-related safety on farms and aims to fill the lack of theoretically based and adequately described behaviour change-based interventions in the relevant literature [ 4 , 12 , 60 ]. Tractor safety is a complex process involving the interactions between tractor design, farmers’ behaviour and environmental factors [ 6 , 19 , 31 ]. The previous studies indicate that the focus of the safety interventions was on increasing the adoption of engineering solutions, introducing safety regulations and raising risk awareness [ 4 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, farm research has relied on introducing technological and regulatory interventions and educational interventions focusing on informing farmers of the risks on farms [ 14 , 15 , 16 ]. However, the normalisation of the danger and persisting risky farm practices indicate a risk awareness to risk prevention behaviour gap [ 17 , 18 , 19 ]. The gap suggests that focusing on improving awareness alone cannot mitigate the potential risks on farms.…”
Section: Introductionmentioning
confidence: 99%
“…ill-health (Landsbergis et al 1999), especially in dangerous occupations such as farming (see, e.g. Alwall et al 2019;Hall 2007), the literature and widespread adoption seem to support the aggregate cost-benefit to performance. Consequently, we propose that farms that adopt a LPO will have better performance measures than those that do not.…”
Section: Lean Production Orientation (Lpo) and Subjective Performancementioning
confidence: 99%
“…A recent review by Nilsson (2016) highlighted a lack of focus on older farmers in the intervention literature and that older farmers are less likely to participate and more likely to drop out of the safety initiatives. Previous studies have also indicated that the risk factors, behavioural practices and motivational factors differ across the age groups (3,13,22).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…This often results in farmers prioritising the risk of financial failure over the risk of their own injuries by working long hours and taking unnecessary risks. These factors also act as barriers to adopting preventative safety behaviours such as routine maintenance activities (13). Hence, a change in the farm operation and farmers' behaviour is required to improve the safety on farms.…”
Section: Introduction Backgroundmentioning
confidence: 99%